Inspecting the total gastrointestinal tract by consecutive bidirectional double-balloon enteroscopy in patients with suspected small bowel bleeding - Zhao, Liang; Yin, Anning; Liao, Fei; Ding, Yijuan; Yu, Honggang (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study aimed to investigate the feasibility, efficiency, and clinical significance of examining the total gastrointestinal (GI) tract by consecutive bidirectional double-balloon enteroscopy (DBE) within 1 day in patients with suspected small-bowel bleeding.Materials and Methods: From January 2016 to January 2018, the clinical and endoscopic data of 41 patients with suspected small-bowel bleeding undergoing DBE aimed at inspecting the total GI tract within 1 day.Results: A success rate of 87.8% (36/41) for examining the total GI tract with no adverse event was achieved by consecutive bidirectional DBE performed within 1 day. The total examination time was 140.61±36.41 (range, 82-270) minutes. Positive or negative findings of bleeding were detected in 51.2% (21/41) and 48.8% (20/41) patients, respectively. Single bleeding etiology with non-small-bowel lesions (NSBLs) or small-bowel lesions (SBLs) was detected in 12.2% (5/41) and 26.8% (11/41) of patients, respectively. Dual bleeding etiologies, including NSBLs and SBLs, were detected in 12.2% (5/41) of patients. A re-bleeding rate of positive or negative findings was different (4.8% vs. 40.0%; p<0.05).Conclusion: Consecutive bidirectional DBE within 1 day can achieve complete vision of the total GI tract with a considerable success rate and high safety. This strategy may provide an option for detecting bleeding etiology throughout the GI tract. A negative finding with this method cannot absolutely exclude missed bleeding etiology and re-bleeding.